Impact of Demonetisation on Bank Stock: A Case of Change in Indian Currency - Triveni P.; Anupma Kumari (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
Demonetisation has impacted the Indian stock market. The benchmark BSE Sensex fell nearly 1.5 per cent and the NSE index fell nearly 2 per cent to its lowest close in six months, dragged down by finance and auto stocks such as State Bank of India and Tata Motors. This paper empirically examines the impact of demonetisation on Indian bank stock. On 8th November 2016, the Indian Prime Minister declared demonetisation in an unscheduled live broadcast. Currency notes of Rs 500 and Rs 1000 were demonetised from the midnight of 8th November 2016. This was issued to curb black money and corruption. During demonetisation, the index values of the stock market SENSEX, NIFTY and BANKEX went down. This research mainly focuses on how demonetisation affected the stock prices of the top Indian banks. The null hypothesis of this study is “no significant effect of demonetisation on S&P BSE BANKEX when compared to S&P BSE SENSEX”. With the help of CAAR, change in return and change in volatility, the effect of demonetisation on the stock market was calculated. Furthermore, an understanding of the impact of demonetisation on bank stocks was attempted. The performance of the banks during pre-demonetisation has indicated that volatility and return are not directly proportional. The evaluation helped in concluding that there has been no impact on the bank stocks post demonetisation. Demonetisation impacted the economy and affected the middle class or merchants since they went cashless. However, it did not affect the stock market.